1999
DOI: 10.1002/(sici)1096-9896(199909)189:1<112::aid-path395>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired structural remodelling of pulmonary arteries in newborns with congenital diaphragmatic hernia: a histological study of 29 cases

Abstract: Congenital diaphragmatic hernia (CDH) is associated in many cases with lung hypoplasia and pulmonary hypertension (PH). The pathogenetic mechanisms underlying the pulmonary hypertension in CDH are not completely understood. In order to alleviate the pulmonary hypertension, new therapeutic modalities have been introduced including extracorporeal membrane oxygenation (ECMO). This paper reports a study of the histology of the lungs of 29 CDH autopsy cases, with special attention to the pulmonary arteries, and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…However, the pulmonary arteries were reduced in size for the airways, making a defect in pulmonary artery development a possible etiology. In lung hypoplasia due to congenital diaphragmatic hernia, where there is a reduced number of airway generations, intrapulmonary artery size is normal relative to the airways and lung volume, but there is an increase in muscular wall and adventitia 16,17 . In renal agenesis, increased pulmonary artery size relative to lung volume has been described 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the pulmonary arteries were reduced in size for the airways, making a defect in pulmonary artery development a possible etiology. In lung hypoplasia due to congenital diaphragmatic hernia, where there is a reduced number of airway generations, intrapulmonary artery size is normal relative to the airways and lung volume, but there is an increase in muscular wall and adventitia 16,17 . In renal agenesis, increased pulmonary artery size relative to lung volume has been described 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that under normal conditions, when approaching full term, pulmonary arteries show reduction in medial thickness [74][75][76]. Molecular basis underlying these changes in pulmonary vasculature during gestation are not known yet.…”
Section: Pulmonary Vasculaturementioning
confidence: 99%
“…The role of vascular smooth muscle cells appears to be crucial [77]. The physiologic reduction in medial thickness when approaching full term was not observed in CDH lungs [76][77][78]. Pulmonary vascular abnormalities in CDH consist of decreased number of pulmonary arteries per unit lung volume and an increase in the medial, adventitial and consequently total wall thickness of all arteries [4,45,[76][77][78][79][80][81].…”
Section: Pulmonary Vasculaturementioning
confidence: 99%
See 2 more Smart Citations